Reference Point Approximation Method for the Solution of Bicriterial Nonlinear Optimization Problems - Jahn, Johannes; Merkel, A. (Journal of Optimization Theory and Applications, 1992)
This paper presents a reference point approximation algorithm which can be used for the interactive solution of bicriterial nonlinear optimization problems with inequality and equality constraints. The advantage of this method is that the decision maker may choose arbitrary reference points in the criteria space. Moreover, a special tunneling technique is given for the computation of global solutions of certain subproblems. Finally, the proposed method is applied to a mathematical example and a problem in mechanical engineering. © 1992 Plenum Publishing Corporation.
UnivIS-Import:2015-03-05:Pub.1992.nat.dma.pama21.refere
Keywords: interactive methods; Multi-objective optimization